Effekte der Konzeption „Lesen durch Schreiben“ auf verschiedene Teilbereiche lauttreuer und orthografischer Verschriftung in der Mitte des ersten Schuljahres - Hess, Miriam; Denn, Ann-Katrin; Kirschhock, Eva-Maria; Lorenz-Krause, Alena; Lipowsky, Frank (Zeitschrift für Grundschulforschung, 2020)
“Reading through writing” by Jürgen Reichen is a concept for written language acquisition in which children learn to write with an initial sound table. The conception is based on the fact that teachers do not correct written language errors. Freely written texts by 507 children from 31 first grade classrooms were evaluated on the basis of a differentiated, qualitative error analysis. Controlling for literacy skills at the beginning of school, multi-level analyses are carried out to determine whether the method has effects on different subareas of phonetic and orthographic spelling. The results show that children whose teachers report a higher importance of the conception “Reading through Writing” in their classroom make more spelling mistakes in total, which can be attributed to differences in orthographic spelling, whereas the number of words that are not correct in phonetic spelling does not differ significantly between the groups.
Keywords: Lesen durch Schreiben; Schriftspracherwerb; Anfangsunterricht; Rechtschreibkompetenz; Unterrichtseffekte